Analysis of association of gene variants with obesity traits in New Zealand European children at 6 years of age. Issue 8 (21st June 2017) - Krishnan, Mohanraj; Thompson, John M. D.; Mitchell, Edwin A.; Murphy, Rinki; McCowan, Lesley M. E.; Shelling, Andrew N.; on behalf of the Children of SCOPE study group, g
Abstract : Childhood obesity is a public health problem, which is associated with a long-term increased risk of cardiovascular disease and premature mortality. Abstract : Childhood obesity is a public health problem, which is associated with a long-term increased risk of cardiovascular disease and premature mortality. Several gene variants have previously been identified that have provided novel insights into biological factors that contribute to the development of obesity. As obesity tracks through childhood into adulthood, identification of the genetic factors for obesity in early life is important. The objective of this study was to identify putative associations between genetic variants and obesity traits in children at 6 years of age. We recruited 1208 children of mothers from the New Zealand centre of the international Screening for Pregnancy Endpoints (SCOPE) study. Eighty common genetic variants associated with obesity traits were evaluated by the Sequenom assay. Body mass index standardised scores (BMI z -scores) and percentage body fat (PBF; measured by bio-impedance assay (BIA)) were used as anthropometric measures of obesity. A positive correlation was found between BMI z -scores and PBF ( p < 0.001, r = 0.756). Two subsets of gene variants were associated with BMI z -scores ( HOXB5-rs9299, SH2B1-rs7498665, NPC1-rs1805081 and MSRA-rs545854 ) and PBF ( TMEM18-rs6548238, NPY-rs17149106, ETV-rs7647305, NPY-rs16139, TIMELESS-rs4630333, FTO-rs9939609, UCP2-rs659366, MAP2K5-rs2241423 and FAIM2-rs7138803 ) in the genotype models. However, there was an absence of overlapping association between any of the gene variants with BMI z -scores and PBF. A further five variants were associated with BMI z -scores ( TMEM18-rs6548238, FTO-rs9939609 and MC4R-rs17782313 ) and PBF ( SH2B1-rs7498665 and FTO-rs1421085 ) once separated by genetic models (additive, recessive and dominant) of inheritance. This study has identified significant associations between numerous gene variants selected on the basis of prior association with obesity and obesity traits in New Zealand European children.